High-performance photocatalytic membranes for water purification in relation to environmental and operational parameters. (1st June 2022) - Homocianu, Mihaela; Pascariu, Petronela
Abstract: Growing technologies, increasing population and environmental pollution lead to severe contamination of water and require advanced water treatment technologies. These aspects lead to the need to purify water with advanced smart materials. This paper reviews the recent advances (during the last 5 years) in photocatalytic composite membranes used for water treatment. For this purpose, the authors have reviewed the main materials used in the development of (photocatalytic membranes) PMs, environmental and operational factors affecting the performance of photocatalytic membranes, and the latest developments and applications of PMs in water purifications. The composite photocatalytic membranes show good performance in the removal and degradation of pollutants from water. Highlights: Recent advances in photocatalytic membranes (PMs) used for water treatment were reviewed. Latest developments and applications of PMs in water purifications were discussed. Photocatalytic membranes show high performance in the degradation of pollutants from water. Scaling-up of the PMs from laboratory scale to pilot-plant and commercial level were analyzed.